Benefit-Cost Analysis, Policy Impacts, and Congressional Hearings. Issue 1 (7th February 2019) - Carlson, Deven; Ripberger, Joseph; Wehde, Wesley; Jenkins-Smith, Hank; Silva, Carol; Gupta, Kuhika; Jones, Benjamin; Berrens, Robert
Abstract : Methods for identifying relevant policy impacts for valuation in benefit-cost analyses (BCAs) have received relatively little attention in academic research, applied policy analyses, and guidance documents. In this paper, we develop a systematic, transparent, and replicable process that draws upon information contained in records of Congressional hearings to identify relevant policy impacts for valuation in a BCA. Our approach involves classifying – and subsequently analyzing – statements from witnesses testifying in Congressional hearings on the topic of the BCA. By using Congressional hearings as the basis for our approach, we are identifying potential policy impacts from information provided during the very process the BCA is intended to inform. However, because this approach is quite resource-intensive and would be somewhat burdensome for agencies to implement, it may be best applied in the academic realm, with identified impacts resulting from such applications then made available to agency personnel for potential inclusion in BCAs. Using the case of the Glen Canyon Dam, we demonstrate the approach and its resulting improvements in the quality and transparency of the BCA it was intended to inform.